2019
DOI: 10.3390/molecules24162914
|View full text |Cite
|
Sign up to set email alerts
|

Diselenides and Benzisoselenazolones as Antiproliferative Agents and Glutathione-S-Transferase Inhibitors

Abstract: A series of variously functionalized selenium-containing compounds were purposely synthesized and evaluated against a panel of cancer cell lines. Most of the compounds showed an interesting cytotoxicity profile with compound 5 showing a potent activity on MCF7 cells. The ethyl amino derivative 5 acts synergistically with cis-platin and inhibits the GST enzyme with a potency that well correlates with the cytotoxicity observed in MCF7 cells. A computational analysis suggests a possible binding mode on the GST en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 68 publications
(80 reference statements)
1
27
0
1
Order By: Relevance
“…However, the study was interrupted before planned, because the data, contrary to the expectation, have not indicated potential beneficial effects of selenium or vitamin E. Despite the negative outcomes of SELECT (Dunn et al 2010 ; Klein et al 2011 ; Lippman et al 2009 ; Nicastro and Dunn 2013 ), the potential use of selenium in cancer prevention or treatment is still a matter of debate (Chapelle et al 2020 ; Vinceti et al 2018 ). Several experimental studies have indicated the potential anti-cancer properties of inorganic and organic forms of selenium (Álvarez-Pérez et al 2018 ; Gandin et al 2018 ; Gopalakrishna et al 2018 ; Krasowska et al 2019 ; Ruberte et al 2019 ; Sanmartín et al 2012 ; Sharma and Amin 2013 ; Spengler et al 2019 ; Steinbrenner et al 2013 ; Tan et al 2019 ). Some clinical studies have also demonstrated that selenite can have beneficial effects by itself or decrease some toxic effects of radiotherapy in cancer patients (Brodin et al 2015 ; Han et al 2019 ; Handa et al 2020 ; Knox et al 2019 ; Muecke et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study was interrupted before planned, because the data, contrary to the expectation, have not indicated potential beneficial effects of selenium or vitamin E. Despite the negative outcomes of SELECT (Dunn et al 2010 ; Klein et al 2011 ; Lippman et al 2009 ; Nicastro and Dunn 2013 ), the potential use of selenium in cancer prevention or treatment is still a matter of debate (Chapelle et al 2020 ; Vinceti et al 2018 ). Several experimental studies have indicated the potential anti-cancer properties of inorganic and organic forms of selenium (Álvarez-Pérez et al 2018 ; Gandin et al 2018 ; Gopalakrishna et al 2018 ; Krasowska et al 2019 ; Ruberte et al 2019 ; Sanmartín et al 2012 ; Sharma and Amin 2013 ; Spengler et al 2019 ; Steinbrenner et al 2013 ; Tan et al 2019 ). Some clinical studies have also demonstrated that selenite can have beneficial effects by itself or decrease some toxic effects of radiotherapy in cancer patients (Brodin et al 2015 ; Han et al 2019 ; Handa et al 2020 ; Knox et al 2019 ; Muecke et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organoselenium compounds are gaining interest in the medicinal chemistry community due to their promising biological activities for a wide range of clinical applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Starting from Ebselen, the first compound showing the ability to function as glutathione peroxidase (GPx) mimetic [ 8 ], several Se-bearing molecules were reported as anticancer [ 9 , 10 , 11 , 12 ], anti-inflammatory [ 13 , 14 ], antidepressant [ 15 , 16 ], and antibacterial [ 17 , 18 , 19 ], among others. Worth mentioning, some of us developed the DiSeBAs class of compounds [ 20 ], endowed with a potent anti-HIV activity due to their ability to inhibit the key viral protein NCp7 [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a growing number of selenium-containing small molecules has been recently demonstrated to possess an array of biological properties, including antioxidant, [23][24][25] anticancer, 26 and enzyme modulator activities. [27][28][29][30][31] The development of novel routes towards organoselenium derivatives is, therefore, highly desirable. 16,32 In this scenario, we recently reported new synthetic procedures for the synthesis of selenium-containing functionalized small molecules under mild conditions.…”
Section: © Author(s)mentioning
confidence: 99%